Aktivitas Antioksidan Nata dengan Substrat Dami Nangka (Artocarpus heterophyllus Lam) dan Kubis Ungu (Brassica oleracea L var. capitata) - Damayanti, Putri G; Mustofa, Akhmad; Karyantina, Merkuria (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
Jackfruit straw and purple cabbage are ingredients that can replace coconut water as a substrate in making nata because they contain nutrients that can be used for the growth of Acetobacter xylinum bacteria. The aim of this research was to determine the characteristics of nata that produce the highest antioxidant activity. The experimental design used is a Completely Randomized Design with two factors. The first factor was the ratio of jackfruit straw to water, (1:1), (2:1), and (3:1), while the second factor was the ratio of purple cabbage to water, (1:1), (2:1), and (3:1). Test parameters included chemical (antioxidant activity, total anthocyanin, moisture, ash, and crude fiber content), physical (weight, yield, thickness, and color lightness (L), redness (a*), yellowness (b*), fermentation media (total sugar content and pH), and organoleptic (color and elasticity) on nata. The results with the highest antioxidant activity were the treatments with a comparison of jackfruit straw extract 3:1 and a comparison of purple cabbage extract 3:1, resulting in antioxidant activity of 41.72%, total anthocyanin of 80.32%, moisture content of 33.29%, ash content of 0.28%, fiber content of 3.10%, weight of 47.86 g, the yield of 9.71%, thickness of 1.34 cm, color L (lightness) 23.09, color a* (redness) 3.17, color b* (yellowness) -5.56. The total sugar content in the media before fermentation was 38.13% with pH 4.2, while after fermentation, the total sugar content was 14.37% with pH 3,1. Extracts of jackfruit straw and purple cabbage in this study were able to increase antioxidant activity in nata.